In vivo confocal microscopy and anterior segment optical coherence tomography follow-up of cysteamine treatment in corneal cystinosis - Ozdemir, Huseyin Baran (Indian J Ophthalmol, 2019)
A 36-year-old female presented initially with photophobia and visual deterioration. After examination and laboratory tests, patient was diagnosed with cystinosis. Cysteamine drops 4 × 1 drops/day was given as treatment for 1 year. During follow-up, in vivo confocal microscopy (IVCM) and anterior segment optical coherence tomography (AS-OCT) was performed. Photophobia was relieved and IVCM obtained the decrease in size and density of corneal crystals 1 year after. Depth of corneal crystals did not change but crystal density score reduced with cysteamine treatment.